Penentuan Kondisi Lingkungan Kerja Fisik yang Optimal Menggunakan Metode Permukaan Respon - Rusidarma Putra, Arta; Guritno, Anggar (Jurnal Sistem dan Manajemen Industri, 2017)
Many consequences caused by the condition of the work environment is not good. This can be caused by noise, lighting and temperature conditions. We need to determine the optimal value of these work environment factors in order to improve operator performance. The correlation between operator performance with work environment factor such as noise, lighting and temperature are found out by develope empirical model to describe relation between operator performance with work environment factor. The model is used to optimize operator performance. This research use surface response method. The experimental design used a central composite design. The research was conducted by experiments in the Laboratory of Analysis of Work Design and Ergonomics of Islamic University of Indonesia Yogyakarta. Variables taken are noise, lighting and temperature. Range for noise is 40 dB to 75 dB, lighting 200 lux to 700 lux, and temperatures between 20ºC to 35ºC. The experiment carried out was the resistor color matching for 5 minutes according to the combination of research variables that have been determined in the surface response method. Output is the number of truths that occur. Using this optimization model, optimal working environment conditions for noise of 60.5 dB, 354.5 lux illumination and temperature of 25.8º.